PENGARUH KOMITMEN PROFESIONAL DAN PERTIMBANGAN ETIS TERHADAP INTENSI MELAKUKAN WHISTLEBLOWING: LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI - Chintya Joneta; Rita Anugerah; Susilatri ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to obtain empirical evidence of the effect of profesional commitment and ethical judgement on the whistleblowing intention. This study also submits the locus of control as moderating variabel that influence the relationship between profesional commitment and ethical judgment . Respondents in this study were 67 auditors who worked in public accounting firm in Sumatera (Pekanbaru, Batam, Medan and Padang) and selected by purposive sampling method. The result of this study indicates: (1) auditor who has higher commitment professional will have more intention to do whistleblowing, (2) auditor who has higher ethical judgement will have more intention to do whistleblowing, 3) but Locus of control has not significant impact to Profesional commitment and Ethical judgement as a moderating.Keywords : Whistleblowing Intention, Commitment Profesional, Ethical Judgement, and Locus Of Control